Brand contact integration in the Ethiopian beer market - Samson Mekonnen; George Angelopulo (Communicare)
This paper assesses Integrated Marketing Communication (IMC) and brand contact integration in three areas that have received insufficient research attention. The study was conducted in a region that has received little research coverage (Ethiopia), a low involvement product sector (brewing) and from the theoretical perspective of the Nordic School. Following a series of in-depth interviews and an inductive content analysis, we find that the brewer’s messaging is similar to the international norm, differing only in emphasis and application. Publicity and personal promotion are emphasised, product quality receives great attention, the company concentrates on a narrowly defined service interface, and a strong market-back strategy is evident in its communications. The Nordic School model of brand contact integration offers a heuristic prism for the assessment of communication integration, and we conclude that IMC principles are firmly embedded in the marketing communication practice of the Ethiopian brewer, but with characteristics that are specific to its unique market conditions.